Gains from trade: Implications for labour market adjustment and poverty reduction in Africa - Augustin Kwasi Fosu; Andrew Mold (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper reassesses the gains from trade for sub-Saharan Africa, and draws their implications for labour market adjustment and poverty reduction. It reviews previous studies on multilateral liberalization, focusing on the findings from computable general equilibrium (CGE) models with relevance to African economies. The implications of these findings for poverty reduction are discussed. Our own CGE exercise supports the hypothesis that African countries cannot expect substantial gains from further multilateral liberalization. Moreover, given the sharp contraction of import-competing sectors in response to trade liberalization in many African economies, coupled with insufficient compensation through labour market adjustments in other sectors, this study suggests that the ultimate impact on poverty reduction is likely to be small or even negative. – trade ; openness ; liberalization ; poverty reduction
Keywords: F16; O24; 330; Außenhandelsliberalisierung; Armut; Allgemeines Gleichgewicht; CGE-Modelling; Afrika